Time-scale-dependent X-ray to UV time lags of NGC 4593 using high-intensity XMM–Newton observations with Swift and AstroSat. Issue 1 (22nd November 2022) - Beard, Max W J; McHardy, Ian M; Kumari, Kavita; Dewangan, Gulab C; Papadakis, Iossif; Bhattacharya, Dipankar; Singh, Kulinder Pal; Kynoch, Daniel; Pahari, Mayukh
ABSTRACT: We present a 140 ks observation of NGC 4593 with XMM–Newton providing simultaneous and continuous pn X-ray and OM UV ( UVW 1 2910 Å) light curves, which sample short-time-scale variations better than previous observations. These observations were simultaneous with 22 d of Swift X-ray and UV/optical monitoring reported previously, and 4 d of AstroSat Soft X-ray Telescope ( SXT ), far (FUV 1541 Å) and near (NUV 2632 Å) UV allowing lag measurements between them and the highly-sampled XMM . From the XMM, we find that UVW 1 lags behind the X-rays by 29.5 ± 1.3 ks, ∼half the lag previously determined from the Swift monitoring. Re-examination of the Swift data reveals a bimodal lag distribution, with evidence for both the long and short lags. However, if we detrend the Swift light curves by LOWESS filtering with a 5 d width, only the shorter lag (23.8 ± 21.2 ks) remains. The NUV observations, compared to pn and SXT, confirm the ∼30 ks lag found by XMM, and after 4 d filtering is applied to remove the long-time-scale component, the FUV shows a lag of ∼23 ks. The resultant new UVW 1, FUV, and NUV lag spectrum extends to the X-ray band without requiring additional X-ray to UV lag offset, which if the UV arises from reprocessing of X-rays implies direct illumination of the reprocessor. By referencing previous Swift and HST lag measurements, we obtain an X-ray to optical lag spectrum, which agrees with a model using the KYNreverb disc-reprocessing code, assuming the accepted mass of 7.63 × 10 6 M⊙ and a spin approaching maximum. Previously noted lag contribution from the BLR in the Balmer and Paschen continua are still prominent.